The Optimal Cutoff Value of Z-scores Enhances the Judgment Accuracy of Noninvasive Prenatal Screening - Zhou, Lingna; Zhang, Bin; Liu, Jianbing; Shi, Ye; Wang, Jing; Yu, Bin (Frontiers in Genetics, 2021)
Objective: To evaluate the accuracy of Z-scores with trisomy 21, 18, 13 and X chromosome aneuploidy of noninvasive prenatal screening. Methods: Among 39310 prenatal women were recruited by NIPS from September 2015 to September 2020. Interventional prenatal diagnosis was applied to verify the diagnosis of NIPS positive results. Logistic regression analysis was employed to relate the Z scores to the PPV of NIPS positive results. Using receiver-operating characteristic (ROC) curves calculated the optimal cut-off value of Z-scores to predict the fetal chromosome aneuploidy. According to the cut-off value, NIPS positive results were divided into Medium Z value group (MZ) and High Z value group (HZ), and then positive predictive value (PPV) were calculated to access Z-scores accuracy. Results: 288 effective values of Z-scores were used as the final data set. The logistics regression analysis revealed that Z-scores were significantly associated with true positive results for T21 and T18 (P<0.05) while for X chromosome aneuploids was not observed (P>0.05). The optimal cut-off value of Z-score with T21, T18, XO, XXX, XXY indicated by ROC curve analysis was 5.79, 6.05, -9.56, 5.89 and 4.47, and the area under curve (AUC) was 0.89, 0.80, 0.48, 0.42 and 0.45 respectively. PPV in HZ group was obviously higher than MZ group and the application of cut-off value reduced the false discovery rate (FDR) which was only 2.9% in HZ group compared with 61.1% in MZ group for T21 and T18. PPV of 3≤Z<5, 5≤Z<10, Z≥10 with T21, T18 and T13 was increased with Z-score. Total PPV in MZ group and HZ group for X chromosome aneuploids was statistically significant. Moreover, the PPV of XXX and XXY were seem to increase with Z-scores except for XO. Conclusion: The Z-score value is helpful for the accurate judgement of NIPS results and the clinical prenatal counseling. Especially for T21 and T18, Z-scores have excellent clinical evaluation which superior to X chromosome aneuploids. In addition, using Z-scores to judge NIPS results offers a certain reference value for XXX and XXY while it seems to be no value for XO.